Training the Social-Emotional Skills of Youth School Students in Physical Education Classes - Malinauskas, Romualdas; Malinauskiene, Vilija (Frontiers in Psychology, 2021)
This study aimed to examine the impact of implementing an innovative Social-Emotional Skills Training Program in physical education classes at youth schools. The study used two surveys: the Schutte Self-Report Inventory (otherwise known as the Emotional Intelligence Scale) and the Social Skills Rating System (student form). The analysis included 104 youth school students (Mage = 16.91; SD = 1.12), who were randomly selected from two youth schools in the Kaunas region. Four classes were randomly assigned into an experimental (n=49) and a control (n=55) group. The experimental group participated in the Social-Emotional Skills Training Program. The intervention was targeted at the following social-emotional skills: empathy, cooperation, assertion, self-control, optimism, ability to understand and analyze emotions, appraisal, and utilization of emotions. The modified physical education classes were conducted by the physical education teacher, who was instructed by the researcher. Repeated measures multivariate analysis of variance was used to analyze the effects of the Social-Emotional Skills Training Program. During the experiment, the applied training procedures had a statistically significant effect on the social-emotional skills of the experimental group of youth school students. Thus, the findings demonstrate that this program (for enhancing social-emotional skills of youth school students) positively impacted students’ social-emotional skills. These results highlight the need to consider social-emotional skills training factors when interpreting the level of social-emotional skills among youth school students.